2002
DOI: 10.1128/jvi.76.6.2899-2911.2002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Adenovirus Vector-Transduced Dendritic Cells, Myoblasts, and Endothelial Cells in Mediating an Immune Response against a Transgene Product

Abstract: Adenovirus-mediated gene delivery via the intramuscular route efficiently promotes an immune response against the transgene product. In this study, a recombinant adenovirus vector encoding ␤-galactosidase (Ad␤Gal) was used to transduce dendritic cells (DC), which are antigen-presenting cells, as well as myoblasts and endothelial cells (EC), neither of which present antigens. C57BL/6 mice received a single intramuscular injection of Ad␤Gal-transduced DC, EC, or myoblasts and were then monitored for anti-␤-galac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
2
37
1
Order By: Relevance
“…Consistent with these findings, CAR ex -VP22 was also more resistant to heat than CAR ex -Tat (data not shown). (16,51), dendritic cells (22,30,33), or neuronal cells (31). As nonepithelial cells express little or no CAR, an acceptable degree of viral infection usually requires very high adenovirus doses, which often impair target cell specific functions and/or result in cytopathic effects due to fiber knob-related toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these findings, CAR ex -VP22 was also more resistant to heat than CAR ex -Tat (data not shown). (16,51), dendritic cells (22,30,33), or neuronal cells (31). As nonepithelial cells express little or no CAR, an acceptable degree of viral infection usually requires very high adenovirus doses, which often impair target cell specific functions and/or result in cytopathic effects due to fiber knob-related toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Nonspecific immune activation likely relates to the fact that adenovirus itself induces an inflammatory response (50), and slightly enhances MHC class 11, CD80, and CD86 expression (Fig. 4), Ag presentation and the T cell stimulatory capacity of transduced DCs (51,52). Although the mechanism(s) of reduction of nonspecific T cell activation by 4-1BBL is not clear, the more highly focused T cell response which occurs when our DC immunogens expressed 4-1BBL is likely to be beneficial in terms of specific vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the exogenous delivery of antigens by bystander cells that are transduced in vivo may result in crosspriming of DC and a more balanced processing into both MHC class I and II. 26,34,35 When Mercier et al 26 compared the direct injection of FG-AdV to vaccination with AdVtransduced DC, they noted relatively similar cellmediated responses after 11 days, but antibody titers were 100-fold higher in the animals that were vaccinated with the FG-AdV in vivo.…”
Section: Helper-dependent Adenovirus Enhanced Vaccine Responses a Harmentioning
confidence: 99%
“…This effect was boosted by a second vaccination and paralleled by the development of anti-b-gal antibodies of the IgG2a isotype, consistent with the induction of a strong Th1 response. 26 Inbred mice are naïve to adenoviral infection and differences in the primary immune response to these two vectors were not likely due to differences in the intensity of antiviral immunity. Consistent with this, we found that mice immunized with either vector developed nearly identical antiviral antibody responses.…”
Section: Helper-dependent Adenovirus Enhanced Vaccine Responses a Harmentioning
confidence: 99%